Seaweed nori (Kappapycus alvarezi) physicochemical and organoleptic characteristics with moringa leaf fortification (Moringa oleifera LAM) - Marleni Limonu; Yoyanda Bait; Adnan Engelen; Nurhayati Muhsin (AGROINTEK, 2024)
Nori was a product made from seaweed which contained fiber and bioactive substances even though it had low antioxidants. The solution was needed to increase antioxidants from Nori products was food diversification with the addition of Moringa leaves which contained high antioxidant activity. Identifying the physicochemical and organoleptic properties of the nori seaweed (Kappapycus alvarezi) with the fortification of Moringa (Moringa oleifera Lam) leaves was the aim of this research. The addition of Kappapycus alvarezi seaweed pulp and Moringa leaf pulp was compared in this study's single-factor randomized design (CRD) four treatments: (K0=100%:0% kontrol), (K1=90%:10%), (K2=80%:20), (K3=70%:30%). The data were evaluated using statistical analysis of variance (ANOVA), and the Duncan Multiple Range Test was used if there was a significant result (p0.05) for each treatment (DMRT). The results showed that Kappapycus alvarezi nori seaweed with fortified Moringa leaves (Moringa oleifera Lam) had an effect on physicochemical and organoleptic characteristics, and could increase the nutritional value of nori, which had an antioxidant activity value of 59.921ppm, total phenol of 252.527%, the water content of 18.030%, Fiber content of 18.637%, thickness test of 0.20 mm, tensile strength/tear strength of 0.541MPa, hydration test of 24.446%. The organoleptic values consist of color at 5.83, aroma at 4.87, taste at 5.03, and texture at 5.53. The impact of this research was to produce products that contained good bioactive substances and antioxidants.